If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 20 = 6x + 13 Reorder the terms: 20 + 8x = 6x + 13 Reorder the terms: 20 + 8x = 13 + 6x Solving 20 + 8x = 13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20 + 8x + -6x = 13 + 6x + -6x Combine like terms: 8x + -6x = 2x 20 + 2x = 13 + 6x + -6x Combine like terms: 6x + -6x = 0 20 + 2x = 13 + 0 20 + 2x = 13 Add '-20' to each side of the equation. 20 + -20 + 2x = 13 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 13 + -20 2x = 13 + -20 Combine like terms: 13 + -20 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| (4x^3+6x-6)+(9x^2-7x+4)= | | x=36/3 | | 8k+20=6k | | 6x^2+10x=-21x-35 | | 14-9x=86-23x | | -2+7x=40 | | x^2-50=-23x | | 4.5+x-4= | | x=9*9 | | x=6*6*6 | | x=2*2*2*2 | | x=2*2*3*5*5 | | 2x^2-36x+162=0 | | x=3*3*3*5 | | -6+23+x= | | (5y+4)(3+y)=0 | | 15x=7x+4 | | -12-x=7 | | 6+23+x= | | 0=2t^2+20t+50 | | x=2*2*2*3*3 | | 0.81-(p^2)=0 | | x=4*4*4*4*4*4*4 | | x=2*2*2*2*2 | | 10.45+x-5= | | x=67+42 | | x=99+56 | | (6x+4)(3x-5)= | | x=83+129 | | 14-x=9 | | x=15*10 | | 12x^3-147x=0 |